First‐in‐man Valve‐in‐Valve with the new balloon‐expandable Myval transcatheter heart valve in a failed sutureless Perceval bioprosthesis. Issue 7 (2nd April 2021) - Belluschi, Igor; Buzzatti, Nicola; Denti, Paolo; Romano, Vittorio; Miceli, Antonio; Alfieri, Ottavio; De Bonis, Michele; Glauber, Mattia; Castiglioni, Alessandro; Montorfano, Matteo
Abstract: Sutureless aortic bioprostheses were introduced more than ten years ago, with the aim of decreasing cross‐clamp time and thus becoming the first choice in older patients for many surgeons. However, published data are limited to a 5‐year follow‐up, and some cases of deterioration have already been described. High‐risk patients who once have benefitted from a fast sutureless aortic replacement and now are experiencing a prosthesis dysfunction, could take advantage of a percutaneous Valve‐in‐Sutureless technique. Furthermore, thanks to technological improvement, new transcatheter prostheses have been designed, allowing a more precise positioning. In this report, we described the first Myval‐in‐Perceval case, which resulted in a safe and effective procedure.